The Influence of Motivation on Employees Performance - Intan Anas Tasya; Alini Gilang (Almana : Jurnal Manajemen dan Bisnis, 2020)
The role of human resources is crucial for the realization of the company's goals to find optimal profits. At this time, employees will be motivated if needs are met, if needs are met then job satisfaction will arise which will have a positive impact on the work needs of employees at the company. This study aims to study the work motivation of employees of PT. Taspen (Persero) Bandung Main Branch Office. The method used in this research is quantitative with a descriptive research type. Respondents in this study were 51 employees of PT. Taspen (Persero) Bandung Main Branch Office, sampling method Saturated sampling technique. Based on the results of research that shows motivation and performance at PT. Taspen (Persero) Bandung Main Branch Office is included in both categories. The results also showed motivation for employee performance. In addition, contributing motivation in contributing to employee performance by 33.8%. So the higher the motivation provided, the higher the employee's performance.